Political Activists as Free-Riders: Evidence from a Natural Field Experiment - Anselm Hager; Lukas Hensel; Johannes Hermle; Christopher Roth (Institute of Labor Economics (IZA), 2019)
How does a citizen's decision to participate in political activism depend on the participation of others? We examine this core question of collective action in a nation-wide natural field experiment in collaboration with a major European party during a recent national election. In a seemingly unrelated party survey, we randomly assign canvassers to true information about the canvassing intentions of their peers. Using survey evidence and behavioral data from the party's smartphone canvassing application, we find that treated canvassers significantly reduce both their canvassing intentions and behavior when learning that their peers participate more in canvassing than previously believed. These treatment effects are particularly large for supporters who have weaker social ties to the party, and for supporters with higher career concerns within the party. The evidence implies that effort choices of political activists are, on average, strategic substitutes. However, social ties to other activists can act as a force for strategic complementarity.
Keywords: D8; P16; 330; political activism; natural field experiment; strategic behavior; beliefs